REGIOSELECTIVE AND CHEMOSELECTIVE BIOCATALYTIC REDUCTION OF α,β,γ,δ-UNSATURATED KETONES BY MARINE-DERIVED FUNGUS Penicillium citrinum CBMAI 1186 - Pedro H. Damada; Pedro H. O. Santiago; Javier Ellena; André L. M. Porto (Química Nova)
Fungi exhibits remarkable adaptability to diverse environments, making them widely distributed across ecosystems. Their vast diversity has driven extensive research into biotechnological applications, including biocatalysis mediated by whole cells or isolated enzymes. Among fungal biocatalysts, marine-derived strains have gained attention due to their unique enzymatic repertoire. In this study, whole cells of Penicillium citrinum CBMAI 1186 were employed to catalyze the selective reduction of α,β,γ,δ-unsaturated ketones into γ,δ-unsaturated ketones. The substrates were synthesized and characterized by nuclear magnetic resonance (NMR) and gas chromatography-mass spectrometry (GC-MS), while crystalline forms were further analyzed via X-ray diffraction. P. citrinum CBMAI 1186 exhibited high catalytic efficiency, achieving conversions exceeding 85% after six days. Fluorineand methyl-substituted compounds displayed faster conversion (1-3 days), suggesting substrate preference. In all cases, only the α,β double bond was reduced, confirming the selectivity of the microorganism for highly conjugated compounds. These discoveries indicate that P. citrinum CBMAI 1186 performs regioselective and chemoselective reductions with high efficiency, establishing its potential as a biocatalyst for selective bioreduction reactions. The exclusive transformation of α,β-unsaturated bonds underscores its applicability in biotechnological processes. Overall, this study highlights the potential of P. citrinum CBMAI 1186 in the development of novel sustainable bioprocesses for fine chemical synthesis.